Intersexual differences in inhibitory influence of trans-resveratrol on activity of cytochrome P450 2D2 in rats - Zendulka, Ondrej; Totusek, Jiri; Sulcova, Alexandra (Neuro endocrinology letters, 2009)
OBJECTIVES: Differences in the metabolism between males and females have been seen over time. Hormonal regulation of cytochrome P450 activity is understood to be involved. Trans-resveratrol (RES) is an estrogenically active plant polyphenol with many protective biological activities including neuroprotection. The present report studied the influence of sex and RES on variances in rat's cytochrome P450 2D2 hepatic metabolic activity. METHODS AND DESIGN: Isolated perfused rat liver was used for determination of cytochrome P450 2D2 activity. Wistar albino rats of both sexes were treated with RES at the dose of 5 mg/kg/day for 10 days prior to liver isolation. Levels of marker substance dextromethorphan (DEM) and its 2D2 specific metabolite dextrorphan (DEX) were measured during perfusion. The metabolic ratios (DEM/DEX) and the levels of DEM and DEX in perfusate were compared. RESULTS: In the controls, the activity of CYP2D2 was found to be higher in male rats compared to females. RES produced inhibition of CYP2D2, expressed by significant changes of both DEM and DEX levels in males and significant increase of only DEM levels in females. There were no gender changes in DEX levels in RES treated animals whilst DEM levels were significantly increased during the whole perfusion in females. CONCLUSION: The results confirmed gender differences in the metabolic activity of CYP450 2D2 with a higher rate in male rats. RES acted as an inhibitor, however again with greater impact in males than in females. This metabolic divergence could be a cause for different sensitivity or even toxicity of drugs metabolized by the CYP450 2D2.
Keywords: Liver; Animals; Female; Rats, Wistar; dextromethorfan; játra; ženské pohlaví; Resveratrol; Enzyme Inhibitors; dextrorfan; stilbeny; Stilbenes; Sex Characteristics; inhibitory cytochromu P450; resveratrol; Male; inhibitory enzymů; Aryl Hydrocarbon Hydroxylases; pohlavní dimorfismus; systém (enzymů) cytochromů P-450; Dextrorphan; krysa rodu Rattus; zvířata; mužské pohlaví; Dextromethorphan; Cytochrome P-450 Enzyme Inhibitors; Rats; Cytochrome P-450 Enzyme System; aromatické hydroxylasy; potkani Wistar